1983
DOI: 10.1007/bf00121192
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of a cathepsin B-like cysteine proteinase in platelet aggregation induced by tumor cells and their shed membrane vesicles

Abstract: Murine 15091A mammary adenocarcinoma cells and membrane vesicles spontaneously shed from these tumor cells in culture can induce aggregation of washed human platelets. A spectrum of proteinase inhibitors was tested for their ability to inhibit 15091A induced platelet aggregation. Of the inhibitors tested the most effective were those selective for cysteine proteinases. The effect of the spectrum of proteinase inhibitors on 15091A induced platelet aggregation was compared to the effect on cathepsin B-like cyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
1

Year Published

1986
1986
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 23 publications
2
25
1
Order By: Relevance
“…Cathepsin B is localised primarily in the lysosomal fraction of normal tissues in a 30-35 kDa precursor form, although activity has also been measured in the plasma membrane fraction of some tumour cells in a 20-kDa mature form (Pietras & Roberts, 1981;Gavanaugh et al, 1983;Koppel et al, 1984;Sloane et al, 1986;Rozhin et al, 1987;Erdel et al, 1990;Weiss et al, 1990). Release of cathepsin B from tumour cells into the plasma membrane and extracellular matrix may be due to a defect in intracellular processing.…”
Section: Discussionmentioning
confidence: 99%
“…Cathepsin B is localised primarily in the lysosomal fraction of normal tissues in a 30-35 kDa precursor form, although activity has also been measured in the plasma membrane fraction of some tumour cells in a 20-kDa mature form (Pietras & Roberts, 1981;Gavanaugh et al, 1983;Koppel et al, 1984;Sloane et al, 1986;Rozhin et al, 1987;Erdel et al, 1990;Weiss et al, 1990). Release of cathepsin B from tumour cells into the plasma membrane and extracellular matrix may be due to a defect in intracellular processing.…”
Section: Discussionmentioning
confidence: 99%
“…The cathepsin B activity in the L-1 fraction of the metastatic B16 melanomas does not appear to be due to a second population of lysosomes (primary or GERL) since plasma membrane fractions isolated from tumor cells of four species by five separate methods have now been shown to possess cathepsin B-like cysteine proteinase activities (12)(13)(14)(15)35 (14) attached a rat anaplastic sarcoma to Affi-Gel 731 beads, disrupted the cells by sonication, and assayed the cell membranes, which remained attached to the beads. Differential centrifugation at high speed (100,000 x g) was used to isolate membrane vesicles spontaneously shed into the culture medium by 15091A murine mammary adenocarcinoma cells (15).…”
Section: Discussionmentioning
confidence: 99%
“…Differential centrifugation at high speed (100,000 x g) was used to isolate membrane vesicles spontaneously shed into the culture medium by 15091A murine mammary adenocarcinoma cells (15). In the present study Percoll density gradient centrifugation was used to purify a plasma membrane fraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, activity (primarily latent) similar to that of cathepsin B, i.e., a cathepsin B-like cysteine proteinase (CB), has been measured in the media of tumor cells and explants in culture [37,38], in the ascites fluid of women with ovarian carcinomas [39] and in the me dia of mammary gland explants [40]. In ad dition, several laboratories including our own have reported that in animal and hu man tumor cells cathepsin B activity is found in association with the plasma mem brane [18, [41][42][43][44][45]. Recently the major ex creted protein (MEP) from transformed mouse fibroblasts has been identified to be a high Mr inactive (acid activatable) precursor of cathepsin L [46][47][48][49][50], Lysosomal enzymes are processed and transported to the lysosomes via receptordependent pathways such as the mannose-6-phosphate pathway [51], This intracellular sorting has been extensively studied in fibro blasts for certain lysosomal enzymes not in cluding cathepsins B and L. Defects in these transport systems have been identified in fibroblasts from patients with lysosomal storage diseases [52] and in some murine tumor cell lines [53,54], In both cases the defect results in increased secretion of lyso somal enzymes.…”
Section: Lysosomal Cysteine Proteinasesmentioning
confidence: 99%